Pengaruh Work-Life Balance dan Burnout terhadap Kepuasan Kerja Karyawan - Indri Iswardhani; Nurdin Brasit; Ria Mardiana (Hasanuddin Journal of Business Strategy, 2019)
The balance of work-life balance and burnout on employee job satisfaction both directly and directly carried out on employees of the Deputy Health BPJS Office in South Sulawesi, West Sulawesi, Southeast Sulawesi, and Maluku. This study uses quantitative variables that investigate the position of the variables proposed and the relationship between one variable with another variable. This research is to test hypotheses that have been formulated previously. This study will explain the causal relationship between variables through hypothesis testing. In this study, the analytical method used is path analysis with an analytical path using the Smart PLS 3.2.8 program. The results of this study found that work-life balance has a positive and significant effect on employee job satisfaction, burnout has a negative and significant effect on employee job satisfaction, a positive work-life balance and a significant effect on employee job satisfaction if mediated by burnout.